Policy for Implementing Housing Development Licensing for Low-Income Communities in Palembang City - Zanariah; Irfan Ridwan Maksum; Eko Prasodjo (International Journal of Science and Society, 2021)
In the context of accelerating housing development for low-income people (MBR), the government makes simplification efforts in simplifying licensing for low-income housing development. To expedite this, the government issued Government Regulation Number 64 of 2016 concerning Low-Income Community Housing Development, then to accelerate its implementation in the regions, it is regulated in Minister of Home Affairs Regulation Number 55 of 2017 concerning Implementation of Licensing and Non-Permitting Housing Development for Low-Income Communities (MBR) in the Region. This study aims to determine government policies related to the implementation of MBR housing development and to determine the performance of the Minister of Home Affairs Regulation Number 55 of 2017 concerning the Implementation of Licensing and Non-Licensing of Housing Development for Low-Income Communities (MBR) in the Regions, especially in the city of Palembang.